Blood Coagulation Simulations using a Viscoelastic Model. (31st July 2014) - Sequeira, A.; Bodnár, T.
Abstract : This paper presents numerical results based on a macroscopic blood coagulation model coupled with a non-linear viscoelastic model for blood flow. The system of governing equations is solved using a central finite-volume scheme for space discretization and an explicit Runge-Kutta time-integration. An artificial compressibility method is used to resolve pressure and a non-linear TVD filter is applied for stabilization. A simple test case of flowing blood over a clotting surface in a straight 3D vessel is solved. This work presents a significant extension of the previous studies [10] and [9].